'Birzhevye Vedomosti' of K.V. Trubnikov: The history of government support of publishing - K.V. Silantev (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper reveals a little-studied episode of the support of the private newspaper “Birzhevye Vedomosti” published by K.V. Trubnikov in St. Petersburg. The purposes of the research are as follows: to resolve the contradiction in the scientific literature about the status of the newspaper “Birzhevye Vedomosti”; to find out using the available documents whether and in which way the newspaper was supported by the government. The methodology used to fulfill the set purposes is traditional for historical investigations: comparative-historical and problem-chronological methods; biographical and descriptive methods; content analysis; method of typology; systemic approach, which has been applied to study the subject of research as a part of the whole, thereby making it possible to show the place and role of the support of K.V. Trubnikov's newspaper in the general process of Russian journalism. It has been established that from the very onset of publication (1861) to 1865 the government, through the Ministry of Finance, supported “Birzhevye Vedomosti”, used the newspaper for its own information-related interests by placing industrial rescripts and messages on the newspaper's pages. Despite the fact that K.V. Trubnikov's newspaper was private during the most period of its existence, its occurrence and first steps were directly associated with the government structures, which largely reflects the realities of print media of that time.